Running into Trouble: An Updated Review of Shin Splints, a Common Running Injury - Rachtan, Magdalena; Radziewicz, Agnieszka; Rudziński, Bartosz; Pyrgies, Agnieszka; Soja, Paulina; Szczuraszek, Dariusz; Sołyga, Dominika; Słowik, Aleksandra; Skoczeń, Olga (Quality in Sport, 2026)
Background: MTSS is an overuse injury of the lower leg, most common in athletes exposed to repetitive loading. It is associated with factors such as excessive pronation and higher BMI. Diagnosis is mainly clinical, and the condition is thought to result from overload and inflammation of the medial tibial periosteum. First-line treatment includes rest and reduction of aggravating activities. Aim: To review and synthesize current knowledge on MTSS, with emphasis on its etiology, pathophysiology, and key risk factors, as well as to evaluate diagnostic methods and outline current treatment and prevention strategies. Materials and methods: A search of PubMed, Embase, Cochrane Library, and Web of Science was conducted to identify recent studies on MTSS, which were then analyzed for etiology, pathophysiology, risk factors, diagnosis, treatment, and prevention. Results: MTSS is a multifactorial overuse condition linked to mechanical overload and biomechanical factors, most common in runners and military populations. Key risk factors include female sex, higher BMI, excessive pronation, and rapid increases in training load. Imaging shows involvement of bone and periosteal tissues, while biomechanical patterns increase tibial loading. Conservative management with load modification is the primary treatment, with limited evidence for adjunctive therapies. Conclusion: MTSS remains an important problem in physically active populations, especially runners and military recruits, and its development appears to result from the interaction of mechanical overload, anatomy, and muscle function. Interventions targeting neuromuscular control and training-load optimization seem most promising for prevention and treatment, and a better understanding of MTSS mechanisms may improve future management. Keywords: shin splints, medial tibial stress syndrome, tibial stress injury, etiology, diagnosis, treatment, prevention, risk factors.